Legal regulation of protection of land rights in Ukraine in the conditions of market transformations - Ignatenko, Iryna; Korniyenko, Ganna; Melnyk, Nataliia; Kupchenia, Lidia (P.A. Persona e Amministrazione, 2025)
The article is dedicated to the constitutional and legal analysis of issues concerning the protection of land rights in Ukraine. The normative enshrinement of property rights is a necessary condition for the functioning of the legal system. The reflection of guarantees for land ownership rights in the Constitution of Ukraine is a primary task. This will create a fundamental basis for existing legislation and ensure comprehensive legal regulation of land relations. Clear normative consolidation of land ownership rights guarantees in the Constitution of Ukraine is a prerequisite for the effective functioning of the land ownership rights protection system. Attention is focused on the fact that the fundamental principles of land relations are declared in the Constitution of Ukraine: the right to land is an absolute right and is guaranteed by the state to the Ukrainian people, and consequently to every citizen. However, not all constitutional principles are properly implemented. The state authorities responsible for establishing the legal regime for all lands must assume responsibility for the full institutionalization of constitutional norms. We conclude that the issues of constitutional protection of land rights remain underexplored and require detailed analysis and justification. The state must strive for excellence and take examples from foreign countries with effective and well-regulated land legislation.